Influence of Different Doses of Butorphanol in Anesthesia with Sevoflurane in Blue-fronted Parrots (Amazona aestiva) - Mendes, Andresa de Cássia Martini; Gomes, Lianna Ghisi; Stocco, Matias Bassinello; Mallmann, Paulo Ricardo; da Paz, Regina Célia Rodrigues; Guimarães, Luciana Dambrósio (Acta Scientiae Veterinariae, 2020)
Background: Parrots frequently require veterinary medical care. To reduce their stress, it is necessary to use chemical restraint or anesthesia. The use of balanced anesthesia techniques such as combinations of inhaled and injectable drugs is recommended. However, there is a shortage of anesthetic and analgesic protocols and data on cardiovascular and respiratory variables in wild birds. The objective of the present study was to evaluate the analgesic, cardiovascular, and respiratory effects and the quality of anesthetic recovery in blue-front parrots (Amazona aestiva) anesthetized with sevoflurane in combination with various doses of butorphanol. Materials, Methods & Results: Twenty-four clinically healthy animals, based on their clinical and hematological results (hematocrit and total plasma protein), were divided into 3 groups: 1- sevofluoran alone (GS); 2- associated with butorphanol at 3 mg/kg (GB3), and 3- 6 mg/kg (GB6) doses administered via the intramuscular (IM) route; digital clamping was used as a nociceptive stimulus. Induction and anesthetic maintenance were performed with sevoflurane at 5 and 2.5 V%, respectively, administered through a calibrated vaporizer and an anesthetic system adequate for the weight of the animals that were kept under spontaneous ventilation. It took 15 min after induction for the expired sevoflurane concentration (EtSevo) to stabilize, after which one intramuscular treatment was applied. The digital clamping was continued as a supramaximal nociceptive stimulus; if it presented a positive response, EtSevo increased by 10%, and when the stimulus decreased by 20%, digital clamping was repeated every 15 min until a positive response to the stimulus was observed. Heart rate (HR) and rhythm, respiratory rate (f), systolic blood pressure (SBP), EtSevo, expired CO2 (EtCO2), and body temperature (T°C) were measured during digital clamping. At the end, anesthetic recovery was evaluated through the extubation times, bipedal positioning, and quality of recovery. Significant statistical differences were observed between the GS and GB6 groups in the variable EtSevo and SBP, with mean ± standard deviation of 2.61 ± 0.48 and 2.17 ± 0.43 V%, and 188 ± 20 and 159 ± 22 mmHg, respectively. The quality of recovery was optimal for all groups, with the mean time ± standard deviation of extubation time of 1.25 ± 0.46, 1.12 ± 0.35, and 1.50 ± 0.92 min, and bipedal positioning of 1.87 ± 1.45, 1.75 ± 0.88, and 2.75 ± 1.28 min for the GS, GB3, and GB6 groups, respectively. Discussion: Balanced anesthesia techniques have demonstrated benefits in veterinary medicine as they reduce cardiovascular and respiratory depression, increase drug potency due to synergism, and require a reduced amount of inhalable anesthetic. The results of this study showed that the combination of sevoflurane and butorphanol at the doses used in the present study reduced the anesthetic concentration necessary for the maintenance of the animals without nociceptive stimulation, respiratory stability, and rapid and quiet anesthetic recovery; it also maintained blood pressure and heart rate within the normal physiological limits. Severe heart rhythm disorders were observed in groups GB3 and GB6, but it is worth mentioning that at the end of anesthesia all animals sinus rhythm. However, the electrocardiographic findings showed that this practice was not considered safe for the species.